2019
DOI: 10.1021/acs.macromol.9b01400
|View full text |Cite
|
Sign up to set email alerts
|

From Local to Diffusive Dynamics in Polymer Electrolytes: NMR Studies on Coupling of Polymer and Ion Dynamics across Length and Time Scales

Abstract: We combine 1 H, 7 Li, and 19 F NMR methods to selectively investigate polymer, cation, and anion dynamics in polymer electrolytes on various length and time scales and over broad temperature ranges. By mixing unentangled poly(propylene glycol) (PPG) with lithium perchlorate (LiClO 4 ) or lithium bis-(trifluoromethylsulfonyl)imide (LiTFSI), fully disordered samples are obtained at all studied concentrations. In static field gradient diffusometry, we observe that the longrange motion of all components slows dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 83 publications
1
19
0
Order By: Relevance
“…Indeed, the measured apparent activation volume closely resembles the ionic volumes of the smaller ions ([Li] + and [Br] − ), suggesting that these ions are responsible for ionic conduction (the ionic volume of [TFSI] − is much greater, Figure a). This finding is at odds with the results from the DFT calculations made in the gas phase as well as with 19 F and 7 Li NMR studies in PPG/LiTFSI and PEO/LiTFSI . The former revealed that [Li] + is always more strongly complexed to the PEO chain as compared to [TFSI] − , whereas the latter identified that [TFSI] − is more mobile than [Li] + with diffusion coefficient ratios of D F / D Li ≈ 4 .…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Indeed, the measured apparent activation volume closely resembles the ionic volumes of the smaller ions ([Li] + and [Br] − ), suggesting that these ions are responsible for ionic conduction (the ionic volume of [TFSI] − is much greater, Figure a). This finding is at odds with the results from the DFT calculations made in the gas phase as well as with 19 F and 7 Li NMR studies in PPG/LiTFSI and PEO/LiTFSI . The former revealed that [Li] + is always more strongly complexed to the PEO chain as compared to [TFSI] − , whereas the latter identified that [TFSI] − is more mobile than [Li] + with diffusion coefficient ratios of D F / D Li ≈ 4 .…”
Section: Resultsmentioning
confidence: 60%
“…51 The former revealed that [Li] + is always more strongly complexed to the PEO chain as compared to [TFSI] − , whereas the latter identified that [TFSI] − is more mobile than [Li] + with diffusion coefficient ratios of D F /D Li ≈ 4. 62 Based on the results from the pressure dependence, we can exclude that [TFSI] − has the major contribution to the ion conduction mechanism. Evidently, the contribution of [TFSI] − to the ionic conduction is diffusionlimited.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is similar to recent experimental results showing that, even in samples with inhomogeneous salt distributions, the product of lithium ion diffusion and polymer relaxation time is temperature-independent in lithium salt-doped poly(propylene glycol). 61 We then normalized cluster relaxation rate by polymer relaxation rate, as shown in Figure 6c. The normalized cluster relaxation rate versus concentration is flat at l B = 0σ, indicating that ion dynamics is highly dependent on polymer dynamics for ions with no electrostatic interactions.…”
Section: Effects Of Coulomb Strengthmentioning
confidence: 99%
“…2,5,6 Another popular approach is pulse-field gradient NMR wherein the Brownian motion of ions is quantified in the absence of an applied potential. 3,[7][8][9][10] In these cases, the translation of ions can be accommodated by segmental relaxation of the polymer chains. 11,12,21,[13][14][15][16][17][18][19][20] Thus, ionic conductivity of a well-studied polymer electrolyte, a mixture of poly(ethylene oxide) (PEO) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt measured by ac impedance spectroscopy, can be explained entirely by the segmental relaxation quantified by quasi-elastic neutron scattering (QENS).…”
mentioning
confidence: 99%
“…A popular approach for characterizing ion transport in electrolytes is ac impedance spectroscopy, which reflects the oscillation of ions in response to a small ac potential. ,, Another popular approach is pulse-field gradient NMR, wherein the Brownian motion of ions is quantified in the absence of an applied potential. , In these cases, the translation of ions can be accommodated by segmental relaxation of the polymer chains. Thus, ionic conductivity of a well-studied polymer electrolyte, a mixture of poly­(ethylene oxide) (PEO) and lithium bis­(trifluoromethanesulfonyl)­imide (LiTFSI) salt measured by ac impedance spectroscopy, can be explained entirely by the segmental relaxation quantified by quasi-elastic neutron scattering (QENS) . To our knowledge, no attempt has been made to study the relaxation processes that govern polymer electrolytes under large applied potentials.…”
mentioning
confidence: 99%